The Historical Works in the XVIIth Reformati Library of S. Casimir Monastery in Cracow (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
This article is the analysis of two library indexes. The inventories date from the XVIIth century (1648and 1671); it describes ownership of library of Cracow monastery S. Casimir. It was a monastery ofmembers of The Order of the Reformati. Each of them contains a historical section “libri historici”.Within them are libri historici sacri and libri historici profani. Here are described historia profana. Thefirst analysis has been dedicated to works of ancient authors, and then — modern. The book collectionsdo not miss any of the leading writers of antiquity (e.g. Titus Livius, Suetonius, Julius Caesar, PliniusSecundus, Tacitus, Plutarchos). Works of modern authors were divided into the following parts: Generalhistory, History of countries and regions, Ancient history through the eyes of humanists, Treatises of thetheory of system, Satirical works, Epistolary, Periodicals, Polish historical writers. The arrangement of thematerial is in such a way that is reveals main historical areas of interest of contemporaries.